The influence of a six-week, high-intensity games intervention on the pulmonary oxygen uptake kinetics in prepubertal obese and normal-weight children - Melitta McNarry (Applied Physiology, Nutrition, and Metabolism, 2015)
Background: The pulmonary oxygen uptake ( O2) response is deleteriously influenced by obesity in pre-pubertal children, as evidenced by a slower phase II response. To date, no studies have investigated the ability of an exercise intervention to ameliorate this. Objectives: To investigate the influence of a six week, high-intensity games orientated intervention on the O2 kinetic response of pre-pubertal obese (OB) and normal-weight (NW) children during heavy intensity exercise. Methods: Thirteen NW and fifteen OB children participated in a twice-weekly exercise intervention involving repeated bouts of 6-minutes of high-intensity, games-orientated exercises followed by 2 minutes of recovery. Sixteen NW and 11 OB children served as a control group. At baseline and post-intervention, each participant completed a graded-exercise test to volitional exhaustion and constant work rate heavy intensity exercise.Results: Post intervention, OB children demonstrated a reduced phase II τ (Pre: 30±8 cf. Post: 24±7 s), MRT (Pre: 50±10 cf. Post: 38±9 s) and phase II amplitude (Pre: 1.51±0.30 cf. Post: 1.34±0.27 l∙min-1). No changes were evident in the NW children. Conclusions: The present findings demonstrate that a six-week, high-intensity intervention can have a significant positive impact on the dynamic O2 response of obese pre-pubertal children.